(untitled) (Baghdad Science Journal, 2025)
Total of 170 samples were collected from Al-Chibayish Marsh reality in Dhi-Qar governorate southern of Iraq to study the epidemology of viral hepatitis in these areas and to detect the type of hepatitis viruses which include A ,B,C,D .The percentage of hepatitis A was 1.17% and most of them below age of ?10 (66.6%) while infection with hepatitis B account 5.29% and includes all age groups. There was no detected cases of hepatitis C,D. The laboratory study showed that the incidence of hepatitis B higher in male (4.11%) compared to female ( 2.35%)